The SAR Angle: A Contemorary Sagital Jaw Dysplasia Marker (Orthodontic Journal of Nepal, 2014)
Introduction: Cephalometric analysis forms the backbone of orthodontic diagnosis and treatment planning. However most of the angles used to assess antero-posterior jaw base discrepancy are based on landmarks that change with age, jaw rotation and orthodontic treatment. Walkers point is one landmark that has been suggested to be stable and easy to locate on radiograph.Objective: To derive SAR angle based on Walkers point, points M and G to assess true sagittal discrepancy.Materials & method: Sixty pretreatment lateral cephalograms of North Indian subjects were grouped in three classes of skeletal pattern based on fulfillment of any two of the three criteria: ANB angle, Witt’s appraisal and Beta angle. The mean and SD for the SAR angle in three groups were calculated. ANOVA one-way of variance and Newman-Keuls tests were done to compare the groups.Result: The mean value for SAR angle of Class I skeletal pattern group was 55.98o (SD 2.24), whereas mean value for Class II and Class III skeletal groups were 50.18o and 63.65o with standard deviations 2.70 and 2.25 respectively. The receiver operating characteristic curves show that the cutoff point between Class I and Class II groups could be considered a SAR angle of approximately 53o, and the cutoff point between Class I and Class III groups could be considered a SAR angle of approximately 59o.Conclusion: The SAR angle can be a reliable diagnostic aid to assess the sagittal jaw discrepancy more consistently.